High human cytomegalovirus DNAemia early post‐transplantation associates with irreversible and progressive loss of renal function – a retrospective study. (15th June 2017) - Lollinga, Wouter T.; Rurenga‐Gard, Lilli; van Doesum, Willem; van Bergen, Rik; Diepstra, Arjan; Vonk, Judith M.; Riezebos‐Brilman, Annelies; Niesters, H. G. M.; van Son, Willem J.; van den Born, Jacob; Sanders, Jan‐Stephan
Summary: Transplant recipients are prone to viral infections, which could affect renal transplantation outcome. Our aim was to assess the effects of early human cytomegalovirus (CMV) DNAemia on transplant renal function. A total of 264 (age 50.9 ± 13.5; male 55%) renal transplantation recipients undergoing preemptive anti‐CMV therapy were retrospectively categorized based on early (<3 months post‐Tx) CMV peak viral load (PVL); PVL ≤ 536, PVL536–6310, or PVL > 6310 International Units/ml (IU/ml). Estimated glomerular filtration rate (eGFR) was analyzed between 1 and 36 months post‐transplantation with Kruskal–Wallis test, linear regression, and a linear mixed‐effects model. CMV infection was detectable in 113 (43%) recipients within 49 [38–67] days. Subjects with PVL > 6310 had statistically significant 5–13 ml/min lower eGFR between 3 and 36 months compared to PVL ≤ 536 and PVL536–6310. eGFR declined from 46.1 to 40.7 ml/min/1.73 m 2 (−12%) over 3 years, and the annual decrease for pronounced infection with high PVL was 2.0 ml/min/1.73 m 2 faster than for noninfected or mildly infected subjects. In conclusion, high CMV DNAemia early after renal transplantation was associated with significant loss of renal function, from which subjects did not recover. The severity of infection (high PVL early post‐transplantation), more than the infection per se, was related to irreversible and progressive loss of renal function.